Improving Students’ Creativity In Mathematic Using SAVI (Somatic Auditory Visual Intellectual) Approach - Ahmad Ahmad; Zulkifley bin Mohamed (AlphaMath : Journal of Mathematics Education, 2021)
The low level of student creativity is a reflection of the unsuccessful learning process. Thus, it needs a special treatment to solve it. The study aims to increase student creativity using the SAVI method for 4th semester students of the Mathematic Education Study Program. This research is a classroom action research. Research with a focus on increasing student creativity using the SAVI method was conducted in semester 4 of the Mathematic Education Study Program, with 44 students. This research was conducted in 3 cycles. After observing and evaluating in 3 cycles with the results mentioned above, it can be concluded that the SAVI learning approach can increase the creativity of students of the UMP FKIP Mathematic Education Study Program. It is proven that in cycle I the average response is 33.71%, in cycle II the average response is 49.3%, and in cycle III the average response is 64.9%. With an increase from cycle I to cycle II of 15.59% and from cycle II to cycle III of 15.6%. From the result it can be said that SAVI was effective to increase students creativity in mathematic.